Analysis of the Use of Modified Coal Bottom Ash as a Media for Immobilization of Microorganisms for the Production of Biogas from Macroalgae - Prastyo, Elli; Ibrahim, Puji Astuti; Solikha, Dian Farkhatus (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2023)
Biofuel from macroalgae is referred to as the third generation biofuel because it does not require fertile land in the production process. Therefore, it is not included in the debate on the food sector. One of the process engineering in biogas production is the addition of immobilization media in anaerobic reactors. Coal combustion produces bottom ash solid waste containing 39.70% carbon (C) and 46.99% silica dioxide (SiO2) as well as other trace metals that have the potential to be used as absorbent materials or immobilization media in anaerobic decomposition. The purpose of this study was to determine the effect of the use of coal bottom ash-based immobilization media in the production of macroalgae biogas Spadina sp. The fixed variable in this study was the use of immobilization media of 30 grams, 40 grams, and 50 grams. Test parameters in the form of sCOD, VFA, biogas volume, and methane levels were used in this study. The production of macroalgae biogas Spadina sp is carried out in a fixed bed reactor with a capacity of 2000 mL with semi-batch conditions. The results showed that the highest biogas production was 204.8 mL/day with the use of immobilization media of 40 grams. The lowest biogas production is 20.5 mL/day with the use of 50 grams of immobilization media. The use of 50 grams of immobilization media is the best media to produce biogas with a high level of purity with an average of 57.48% followed by the use of 40 grams of immobilization media with an average of 41.35%, and the use of 30 grams of immobilization media with an average of 21.96%.